Tantangan dan Solusi Pengelolaan Basis Data: Dari Keamanan Hingga Optimalisasi Query - Zelly Apriza; Tata Sutabri (JOURNAL SAINS STUDENT RESEARCH, 2025)
Databases are a vital component in information management across various sectors. However, several challenges are often encountered, such as threats to data security, inefficiencies in data processing, and suboptimal query performance. This journal presents a review of various techniques that can be employed to address these challenges, including the use of parameterized queryes to prevent SQL injection attacks, data encryption during backup and restore processes, and query optimization through search algorithms, indexing, and heuristic approaches such as genetic algorithms in the context of distributed databases. Based on several recent studies, this research concludes that integrating security methods and optimization techniques can significantly improve the performance and reliability of modern database systems